Correlation between Blood Types and Intraabdominal Infection: A Preliminary Study - Robby, Rizky DK.; Moenadjat, Yefta (The New Ropanasuri Journal of Surgery, 2018)
Introduction. Intra-abdominal infection (IAI) remain a clinical problem with high mortality rate. Among factors contributed to this mortality, the important one is blood type that never be considered. It was thought to have correlation with a certain type. Thus, a retrospective study as a preliminary study run to find out the evidence. Method. A descriptive analytic with cross sectional design was run. Data of those diagnosed with intraabdominal infection due to abdominal trauma and gastrointestinal infections managed at dr Cipto Mangunkusumo General Hospital was taken from medical record. ABO blood types and microbial culture results in two groups were the focus of a study and were analyzed statistically. Results. In the study, out of 230 subjects, there were 22 subjects (9.6%) with postoperative intra-abdominal infection were observed during January 2014-March 2016. There was a significant correlation between blood transfusion (p <0.001, OR = 0.02) with intraabdominal infection. However, there was no significant correlations found in blood type to the occurrence of intra-abdominal infection. Conclusion. The study unable to show that blood type has a correlation to intra-abdominal infection in those diagnosed with abdominal trauma and gastrointestinal infections.